Answer :

First term = a

Sum up to first term = a


Last term (nth term) = an


Sum up to n terms = Sn


Second last term = an–1


Sum up to (n–1) th term = sn–1


Therefore, an = Sn–Sn–1


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Arithmetic Progression- Don't miss these QuestionsArithmetic Progression- Don't miss these QuestionsArithmetic Progression- Don't miss these Questions56 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses